Perancangan Dan Pembuatan Aplikasi Rumah Makan Kabayan Kota Bengkulu Berbasis Web - Yetman Erwadi; Sri Handayani; Ahmad Muchsin (Universitas Janabadra, 2022)
A restaurant is a place of business whose scope of activity is to provide food and beverage services to the public at its place of business. One of the restaurants that became the object of research in this final project is the Kabayan restaurant which provides a variety of food menus. In this restaurant service is still conventional in that the service for ordering food still uses paper media to record the order so that it allows errors due to negligence of the waiter, as well as the lack of notification for customers about food availability and information on the status of the food menu. This causes the food menu process to be less effective. Therefore a food menu application was built that can minimize the problems that occur in the process of selecting food and provide the information needed by customers and owners so that it can improve service. This application was built using the waterfall system development method and UML modeling, with the PHP programming language and database creation using MySLQ. In implementing this application, customers can make food menus that have been provided by the restaurant owner.